2013
DOI: 10.1093/brain/awt102
|View full text |Cite
|
Sign up to set email alerts
|

Brain communication in the locked-in state

Abstract: Patients in the completely locked-in state have no means of communication and they represent the target population for braincomputer interface research in the last 15 years. Although different paradigms have been tested and different physiological signals used, to date no sufficiently documented completely locked-in state patient was able to control a brain-computer interface over an extended time period. We introduce Pavlovian semantic conditioning to enable basic communication in completely locked-in state. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 41 publications
0
55
1
Order By: Relevance
“…Moreover, with one exception (Gallegos-Ayala et al, 2014), patients lacking control of all muscles (e.g., completely locked-in patients) have been entirely unsuccessful in maintaining control over neuroimaging signals (De Massari et al, 2013).…”
Section: Megmentioning
confidence: 99%
“…Moreover, with one exception (Gallegos-Ayala et al, 2014), patients lacking control of all muscles (e.g., completely locked-in patients) have been entirely unsuccessful in maintaining control over neuroimaging signals (De Massari et al, 2013).…”
Section: Megmentioning
confidence: 99%
“…Alternatively, visual P300 or steady-state visual evoked potential (SSVEP) from EEG can also be used for BCI systems [19], [20], but these fast visual BCI requires full engagement of the users' gaze control, which can be challenging and undesirable in real-life application settings. It is suggested that auditory and proprioceptive BCIs are the only remaining channels of communication for many potential BCI users, such as those in the late stage of amyotrophic lateral sclerosis (ALS) [21]- [23]. By requiring the active involvement of the somatosensory system, somatosensory stimulation might also provide a way to avoid the "extinction of thought" [24].…”
Section: Introductionmentioning
confidence: 99%
“…A limiting factor for the use of a traditional SMR based BCI is that vision must not be compromised in the end-user. For instance, several studies showed that in the last stage of ALS (i.e., completely locked-in) the visual sensory channel cannot be used as a reliable BCI input (De Massari et al, 2013;Murguialday et al, 2011). Sensorimotor rhythms (SMR) refer to localized sinusoidal frequencies in the upper alpha band (10-12 Hz) usually accompanied by changes in synchronization in the beta band (13-25 Hz) (Pfurtscheller and Neuper, 2001), which can be recorded over primary somatosensory and motor cortical areas.…”
Section: Introductionmentioning
confidence: 99%
“…Motor imagery is defined as the mental simulation of a kinesthetic movement (Decety and Inqvar, 1990;Neuper et al, 2005). Signal processing algorithms, individual users' characteristics, such as psychosocial and physiological parameters (e.g., fine motor skills) or brain structures, can predict performances for SMR-based BCIs Halder et al, 2011Halder et al, , 2013Hammer et al, 2011;Randolph, 2012). Besides these factors, feedback is a necessary feature for initial learning of the BCI skill (Brown, 1970;Kuhlman, 1978;McFarland et al, 1998;Wolpaw et al, 1991Wolpaw et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%